Study of the Addition Hull of Mung Bean Sprouts Extract to pH and Characteristic of Sensory Yogurt Probiotic - Syifa Khairunnisa; Indira Lanti Kayaputri; Gemilang Lara Utama (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2019)
This research aims to determine the effect of adding hull of mung bean sprouts extract to pH and characteristics of sensory yogurt probiotic. The research method used experimental with randomized block design. There were 4 additional treatments (1%, 2%, 3%, and 4% w /v hull of mung bean sprouts extract) with 3 replications. The data obtained will be tested further using the Duncan test. The addition hull of mung bean sprouts extract has a significant different effect on the pH and color characteristics of yogurt probiotic while giving no significant effect on the characteristics of aroma, taste, texture and overall acceptance. Addition hull of mung bean sprouts extract affects the pH of yogurt probiotic produced which is about 4.00 - 4.11. The color preferences of the yogurt probiotic are on the scale of dislike – really likes and preferences of the aroma, taste, texture and overall acceptance of yogurt probiotic are on the scale of usual - like. The conclusion of this study is that the addition hull of mung bean sprouts extract can prevent a decrease in pH, causing a decrease in the level of preference for color and yogurt probiotic that produced is acceptable to consumers.